Effect of the Arch Support on the Strength of the Abductor Hallucis During the Toe Spread Out Exercise in Standing Position in Individuals With Pes Planus - In-cheol Jeon; Ki-song Kim (Physical Therapy Korea, 2020)
Background: The longitudinal arch is important for individuals with pes planus. The toe spread out exercise (TSO) has been widely used to continuously support the longitudinal arch by increasing the abductor hallucis (AbdH) muscle activation. However, the AbdH muscle is commonly lack of the sufficient activation during the TSO especially in individuals with pes planus. Objects: This study was performed to investigate the effect of arch support on the muscle activity and strength of the AbdH during TSO in standing position in individuals with pes planus. Methods: Twenty subjects with pes planus between 20 and 30 years of age participated in this study. The muscle activity and strength of the AbdH were measured using surface EMG system and the Smart KEMA tensiometer system. The AbdH muscle was evaluated during TSO between individuals with and without longitudinal arch support in standing position. The longitudinal arch was supported by using the insole. The paired t-test was used. The level of statistical significance was set at α = 0.05. Results: The muscle activity and strength of the AbdH during TSO with arch support in standing position was significantly greater than that without arch support. Conclusion: The muscle activity and strength of the AbdH during TSO in standing position can be influenced by the longitudinal arch support in individuals with pes planus. The AbdH strengthening during TSO in standing with arch support can be recommended especially in individuals with pes planus in the clinical settings.